Control de existencias y su relación con la gestión rentable en una distribuidora de alimentos - Lima Amado, Debbie Alissa (2024)
This research analyzes the relationship between inventory control and the profitable management of the company D'Rose Concesiones E.I.R.L. in Arequipa in the year 2023. Regarding the methodology, the study has been quantitative and applied, in addition, it was decided to adopt a cross-sectional correlational level. The research consisted of a population of 50 individuals working in the entity, to whom a questionnaire was applied to gather information on the application of stock control and profitable management, this instrument was validated by expert judgment and its reliability was determined based on Cronbach's Alpha. In the results, it was found that the relationship between the variables is high and significant, therefore, the research hypothesis was accepted, since a Spearman's Rho value of 0.989 and a significance level of 0.000 were observed; additionally, a Spearman's coefficient value greater than 0.9 and a significance level of 0.000 were observed, which shows the strong and significant link between economic, financial and commercial profitability. To conclude, the research culminates with the confirmation of the relevance of an efficient stock control to optimize the profitable management in the company D'Rose Concesiones E.I.R.L, in addition, adopting such actions will bring about a correct stock storage and higher profitability.